Txt2stop: a pilot randomised controlled trial of mobile phone-based smoking cessation support. Issue 2 (24th March 2009) - Free, C; Whittaker, R; Knight, R; Abramsky, T; Rodgers, A; Roberts, I G
Abstract : Aim: To conduct a pilot randomised controlled trial of mobile phone-based smoking cessation support intervention for the UK population. Design: Randomised controlled trial (txt2stop). Setting: Community. Participants: 200 participants responding to radio, poster and leaflet-based promotions regarding the trial. Main outcome measures: The response rate for the outcome measures planned for the main trial. Participants' qualitative responses to open-ended questions about the intervention content. Secondary outcomes were the outcomes planned for the main trial including the point prevalence of self-reported smoking at 4 weeks and pooled effect estimate for the short-term results for the STOMP and txt2stop trials. Results: The response rate at 4 weeks was 96% and at 6 months was 92%. The results at 4 weeks show a doubling of self-reported quitting relative risk (RR) 2.08 (95% CI 1.11 to 3.89), 26% vs 12%. The pooled effect estimate combining txt2stop and a previous New Zealand trial in the short term is RR 2.18 (95% CI 1.79 to 2.65). Conclusions: Mobile phone-based smoking cessation is an innovative means of delivering smoking cessation support, which doubles the self-reported quit rate in the short term. It could represent an important, but as yet largely unused, medium to deliver age-appropriate public health measures. The long-term effect of this mobile phone-based smoking cessation support will be established by a large randomised controlled trial currently in recruitment.